Information and incentives: the economics of carrots and sticks (1997)
THE INVISIBLE HAND: In a lecture that will deal chiefly with ignorance, it may seem natural to begin with Adam Smith’s most famous contribution to economics, his vision of in-dependent selñsh beings who by living and working together in the economic system somehow do what is best for one another. First, in The Theory 0fMoml Sentiments, he said "The rich only select from the heap what is most precious and agreeable. They consume little more than the poor, and in spite of their natural selfishness and rapacity ...they divide with the poor the produce of all their improvements. They are led by an invisible hand to make nearly the same distribution of the necessaries of life which would have been made, had the earth been divided into equal portions among all its inhabitants. (W.i.10).